1982
DOI: 10.2118/8323-pa
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Oil Recovery Observations on a Series of Synthetic Petroleum Sulfonates

Abstract: Synthetic sulfonates for application in enhanced oilrecovery are of increasing interest. Because of the needto explore the range of candidates potentially available atvarious costs from the petrochemical industry, a series ofnine samples was prepared for distribution with financial suppose of the U.S. DOE. This paper briefly describesthe samples and, in more detail, the characterization ofthe samples for oil recovery. The characterization included determination of optimal salinity, stability ofaqueous dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The investigation of alkaline EOR has been widely addressed. It has been shown that the added alkali will react with the acidic groups of the crude oil to generate interfacially active components called in situ surfactants that accumulate at the oil/water interface and reduce the IFT. For surfactant-enhanced alkaline/acidic oil, most studies deal with acidic crude oil or a model oil obtained by the addition of fatty acids to the oil phase, to simulate an acidic crude oil. The addition of alkaline chemicals is very beneficial for reducing the retention of anionic surfactants to the rock surface and lowering IFT. It has been shown that the addition of a properly chosen water-soluble surfactant to the alkaline additives raises the concentration of electrolyte required for minimum IFT (optimum salinity) for optimal oil recovery and that the optimal salinity decreases with increased surfactant molecular weight or increased surfactant concentration . Martin et al investigated a surfactant-enhanced alkali/sand oil [36.7° American Petroleum Institute (API)] system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of alkaline EOR has been widely addressed. It has been shown that the added alkali will react with the acidic groups of the crude oil to generate interfacially active components called in situ surfactants that accumulate at the oil/water interface and reduce the IFT. For surfactant-enhanced alkaline/acidic oil, most studies deal with acidic crude oil or a model oil obtained by the addition of fatty acids to the oil phase, to simulate an acidic crude oil. The addition of alkaline chemicals is very beneficial for reducing the retention of anionic surfactants to the rock surface and lowering IFT. It has been shown that the addition of a properly chosen water-soluble surfactant to the alkaline additives raises the concentration of electrolyte required for minimum IFT (optimum salinity) for optimal oil recovery and that the optimal salinity decreases with increased surfactant molecular weight or increased surfactant concentration . Martin et al investigated a surfactant-enhanced alkali/sand oil [36.7° American Petroleum Institute (API)] system.…”
Section: Introductionmentioning
confidence: 99%
“…19À21 The addition of alkaline chemicals is very beneficial for reducing the retention of anionic surfactants to the rock surface and lowering IFT. It has been shown that the addition of a properly chosen water-soluble surfactant to the alkaline additives raises the concentration of electrolyte required for minimum IFT (optimum salinity) for optimal oil recovery 3 and that the optimal salinity decreases with increased surfactant molecular weight 22 or increased surfactant concentration. 23 Martin et al 16 investigated a surfactant-enhanced alkali/sand oil [36.7°American Petroleum Institute (API)] system.…”
Section: ' Introductionmentioning
confidence: 99%